Photonic transport network architecture and OA&M technologies to create large-scale robust networks. - Okamoto, S. (IEEE Journal on selected areas in communications)
In order to realize a large-scale and robust photonic transport network, a network protection strategy and operation, administration, and management (OA&M) realization scheme in wavelength division multiplexing optical path (WDM OP) transport networks has been developed. This paper discusses the networking (restoration/protection) concepts in each optical layer and proposes the most suitable networking strategy. To develop the OA&M technique, the characteristic information format of each optical layer must be discerned. A network node interface (NNI) structure for the WDM OP transport network is proposed. The proposed NNI is defined as the optical transport module (OTM). An OP signal format is defined as the optical transport unit (OTU). Overhead information and schemes to transmit it are also discussed